Human resource management in multinational companies: global and local challenges - A. V. Chernov; V. A. Chernova; A. A. Kogan (Вестник университета, 2022)
This article examines a cross-section of the problems associated with human resources management in multinational companies that HR department managers face in their practice. Since the second half of the 20th century, transnational corporations began to enter foreign markets and face the challenges posed by culturally diverse staff at subsidiaries. Until now, the problems of human resource management in a cross-cultural environment have not lost their relevance. The authors cover the issues of human resource management policies standardization/ adaptation in multinational companies, cultural differences as a necessary condition for human resource management, intercultural communications. This study aimed to help managers of human resource management departments of multinational companies to remove obstacles and see new opportunities for HR management in an intercultural environment.